Financial risk management : models, history, and institutions - Malz, Allan M. (Wiley finance series, 2011)
"An in-depth look at the tools and techniques professionals use to address financial risksRisk and uncertainty, as Allan Malz explains in his ground-breaking new book, are two completely different concepts. Risk is a quantifiable uncertainty that can be modeled, while uncertainty defines non-quantifiable outcomes that are not always known. Part art and part science, the study of risk remains a relatively new discipline in finance and economics that continues to be refined. Financial crisis, rather than destroying the need for risk management, has given even great nuance and meaning to what risks exist and can be managed and controlled, and a taxonomy of new risks that need to be explored in ever more meaningful ways. This definitive guide on financial risk Explores all the tools and techniques needed to cope with risk Addresses state of the art approaches to modeling and managing risks Investigates stress tests in periods of heightened uncertainty, and the impact that variables such as liquidity and correlations can have on risk mitigation Provides practicing risk professionals with useful rules of thumb, intuitions, and insights gleaned from Malz?s entire career as risk researcher, chief risk officer, and financial market regulator outside his classroom at Columbia University Informative and engaging, this book will help you understand why risk has become its own essential discipline on Wall Street and beyond"-- Provided by publisher